Randomized Trial of a Decision Aid for BRCA1/BRCA2 Mutation Carriers: Impact on Measures of Decision Making and Satisfaction - Schwartz, Marc D. (2009)
OBJECTIVE: Genetic testing is increasingly part of routine clinical care for women with a family history of breast cancer. Given their substantially elevated risk for breast cancer, BRCA1/BRCA2 mutation carriers must make the difficult decision whether or not to opt for risk reducing mastectomy. To help BRCA1/2 carriers make this decision, we developed a computer-based interactive decision aid which we tested against usual care in a randomized controlled trial. DESIGN: Following the completion of genetic counseling, 214 female (aged 21–75) BRCA1/BRCA2 mutation carriers were randomized to Usual Care (UC; N=114) or Usual Care plus Decision Aid (DA; N=100) arms. UC participants received no additional intervention. DA participants were sent the CD-ROM decision aid to view at home. MAIN OUTCOME MEASURES: We measured final management decision, decisional conflict, decisional satisfaction and receipt of risk reducing mastectomy at 1-, 6-, and 12-months post-randomization. RESULTS: Longitudinal analyses revealed that the DA was effective among carriers who were initially undecided about how to manage their breast cancer risk. Within this group, the DA led to an increased likelihood of reaching a management decision (OR=3.09, 95% CI=1.62, 5.90; p<.001), decreased decisional conflict (B=−.46, z=−3.1, p<.002), and increased satisfaction (B=.27, z=3.1, p=0.002) compared to UC. Among carriers who had already made a management decision by the time of randomization, the DA had no benefit relative to UC. CONCLUSION: These results demonstrate that BRCA1/BRCA2 mutation carriers who are having difficulty making a breast cancer risk management decision can benefit from adjunct decision support.